2017
DOI: 10.3390/jcm6050055
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Interleukin-18, Oxidative Stress and Metabolic Syndrome in Alzheimer’s Disease

Abstract: The role of interleukins (ILs) and oxidative stress (OS) in precipitating neurodegenerative diseases including sporadic Alzheimer’s disease (AD), requires further clarification. In addition to neuropathological hallmarks—extracellular neuritic amyloid-β (Aβ) plaques, neurofibrillary tangles (NFT) containing hyperphosphorylated tau and neuronal loss—chronic inflammation, as well as oxidative and excitotoxic damage, are present in the AD brain. The pathological sequelae and the interaction of these events during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 167 publications
1
19
0
1
Order By: Relevance
“…We also found that HFD-fed mice showed significantly increased plasma triglyceride, cholesterol, and significantly lower adiponectin levels compared with their respective control mice (Figure 1b-d). Other studies have shown that high-fat-diet-induced obesity in mice exhibited lower glucose and insulin tolerance versus normal-diet mice [48]. Similarly, the HFD-fed mice showed a significant decrease in insulin sensitivity, as demonstrated by the GTT and ITT results (Figure 1e,f).…”
Section: Hfd-induced Obesity Deregulates Metabolic Parameters In Micesupporting
confidence: 55%
“…We also found that HFD-fed mice showed significantly increased plasma triglyceride, cholesterol, and significantly lower adiponectin levels compared with their respective control mice (Figure 1b-d). Other studies have shown that high-fat-diet-induced obesity in mice exhibited lower glucose and insulin tolerance versus normal-diet mice [48]. Similarly, the HFD-fed mice showed a significant decrease in insulin sensitivity, as demonstrated by the GTT and ITT results (Figure 1e,f).…”
Section: Hfd-induced Obesity Deregulates Metabolic Parameters In Micesupporting
confidence: 55%
“…Injuries to the brain evoked inflammatory responses and the activation of astrocytes and microglia [48,49]. Therefore, in the present study, using western blot analysis, we examined the activation of inflammatory mediators in the ipsilateral side of the treated mice, at day 7.…”
Section: Resultsmentioning
confidence: 99%
“…ROS damage cell membranes and increase their rigidity, leading to modifications in proteins, lipids, and cell membrane receptors. With respect to the latter, this alters their function, intracellular signaling, and clustering with other membrane receptors [ 51 ]. Oxidative stress and ROS production can result in cellular damage when constructing the molecular basis, and thus can also result in the progression of a number of neurodegenerative diseases [ 52 , 53 , 54 , 55 , 56 ].…”
Section: Nuclear Factor (Erythroid-derived 2)-like 2 (Nrf2) and Nementioning
confidence: 99%